THE EFFICACY AND SAFETY OF SILODOSIN FOR THE TREATMENT OF BENIGN HYPERPLASIA PROSTATE: A SYSTEMATIC REVIEW - Sapta Putra, Steven (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: BPH is a prevalent and costly condition affecting the quality of life for older men. adrenoceptor antagonists provide effective relief for bothersome symptoms but do not prevent the need for surgery or acute urinary obstruction. Silodosin, newer adrenoceptor antagonist, offers comparable symptom relief to tamulosin Aim: This systematic review evaluates the efficacy and safety of silodosin for the treatment of benign prostatic hyperplasia (BPH) and its suitability for daily clinical practice.. Methods: This systematic review examined the use of silodosin in men with benign prostatic hyperplasia (BPH). Multiple databases were searched for relevant literature. (PubMed and Cochrane Library) Results: This systematic review included four randomized trials involving 2504 patients with benign prostatic hyperplasia. The analysis showed that silodosin demonstrated significant improvements in International Prostate Symptom Score, specifically in storage and voiding symptoms, compared to placebo. Conclusion: Silodosin shows efficacy and safety for treating benign prostatic hyperplasia (BPH), but the higher incidence of retrograde ejaculation warrants further high-quality, long-term studies, including direct comparisons with tamsulosin.